Employee commitment in Ghanaian healthcare: a multi-factor analysis - Yamoah, Emmanuel Erastus (Business, Management and Economics Engineering, 2025)
Purpose – The study investigates the factors influencing organizational commitment among employees at a Municipal Health Directorate (MHD) in Ghana. It focuses on identify- ing key organizational and individual factors that drive commitment and examining potential gender differences. Research methodology – A quantitative approach was employed, using a cross-sectional survey of 204 MHD employees, with a final sample size of 153. A structured questionnaire measured organizational commitment and influencing factors. Multiple regression analysis was used to examine relationships between variables. Findings – Key drivers of commitment include training and development, salary, leadership style, work environment, job satisfaction, and involvement in decision-making. Training and development were the strongest predictors of commitment, while job-related stress negatively influenced commitment. No significant gender differences in commitment were found. Research limitations – The cross-sectional design limits causality. Future research should adopt longitudinal designs to track changes in commitment over time and explore gender differences in other contexts. Practical implications – The findings emphasize the importance of investing in employee development, fostering supportive leadership, managing job stress, and involving employees in decision-making to enhance commitment. Originality/Value – This study provides valuable insights into the determinants of employee commitment in healthcare, contributing to the limited research on organizational commitment in resource-constrained healthcare settings in Ghana.